Growth characteristics and therapeutic decision markers in von Hippel-Lindau disease patients with renal cell carcinoma - Schuhmacher, Patrick; Kim, Emily; Hahn, Felix; Sekula, Peggy; Jilg, Cordula Annette; Leiber, Christian; Neumann, Hartmut P.; Schultze-Seemann, Wolfgang; Walz, Gerd; Zschiedrich, Stefan (Orphanet journal of rare diseases, 2019)
Background Von Hippel-Lindau (VHL) disease is a multi-systemic hereditary disease associated with several benign and malignant tumor entities, including clear cell renal cell carcinoma (ccRCC). Since ccRCCs grow slowly, nephron sparing surgery is typically performed at a tumor diameter of 3–4 cm before the tumor metastasizes. However, in the case of recurrent disease, repeated surgical intervention can impair renal function. Therefore, it is crucial to optimize the timing for surgical interventions through a better understanding of the growth kinetics of ccRCCs in VHL. We investigated tumor growth kinetics and modern volumetric assessment to guide future therapeutic decisions. Results The prevalence of ccRCC was 28% in a cohort of 510 VHL patients. Of 144 patients with ccRCC, 41 were followed with serial imaging which identified 102 renal tumors, which exhibited heterogeneous growth kinetics. ccRCCs grew at an average absolute growth rate of 0.287 cm/year, an average relative growth rate [ (lnV 1 -lnV 0 )/(t 1 -t 0 ) ] of 0.42% and an average volume doubling time of 27.15 months. Women had a faster relative growth rate than men. Age and specific mutations did not influence tumor growth. Because of the tumor heterogeneity, we developed an additional cut-off volume of 40 cm 3 for surgical intervention. Conclusions Tumor heterogeneity and differences in growth kinetics is suggestive of a state of transient tumor dormancy in ccRCCs of VHL patients. The relative growth rate has not been previously described in other studies. Volumetric assessment as an additional parameter for surgical intervention could be a useful clinical tool and needs further investigation.